Clinical Characteristics of Non-Puerperal Mastitis: A Retrospective Analysis of 724 Patients - Feng J; Gao Q; Qu W; Shao S; Sun J; Xie L; Wu X; Wan H (International Journal of Women's Health)
Jiamei Feng, Qingqian Gao, Wenchao Qu, Shijun Shao, Jiaye Sun, Lu Xie, Xueqing Wu, Hua Wan Department of Mammary, Shuguang Hospital Affiliated to Shanghai University of Tradition Chinese Medicine, Shanghai, 200011, People’s Republic of ChinaCorrespondence: Hua Wan; Xueqing Wu, Department of Mammary, Shuguang Hospital Affiliated to Shanghai University of Tradition Chinese Medicine, Shanghai, 200011, People’s Republic of China, Tel +86 21 53827363, Fax +86 21 20256699, Email wanhuawhhhf@126.com; wuxueqingwxq02@126.comObjective: The aim of this study is to retrospectively analyze the clinical characteristics of non-puerperal mastitis.Methods: A retrospective study was undertaken to investigate 724 cases of non-puerperal mastitis in patients hospitalized from April 2004 to December 2021 at the Mammary Gland Department of Shuguang Hospital, which is affiliated with Shanghai University of Traditional Chinese Medicine. Employing statistical methodologies including mean ± standard deviation, median, and one-sample t-test, the study sought to analyze and delineate factors associated with morbidity, such as age, childbirth, lactation, and body mass index (BMI).Results: The average age of the 724 patients was 33.4 ± 5.5 years. Among them 54.94% were aged 30– 39 years, 65.16% were within five years after delivery, and 62.56% were breastfeeding for less than 6 months. The BMI of patients aged 30– 39 years was higher than that of the general Chinese population (P < 0.05). There was no significant correlation between smoking, oral contraceptives, trauma, and the incidence of the disease in this group.Conclusion: Non-puerperal mastitis is more prevalent among women of childbearing age, specifically those aged 30– 39 years, who breastfed for less than 6 months within the first five years after childbirth. In this age group, higher BMI is linked to increased morbidity.Keywords: mastitis, clinical feature, non-puerperal, retrospective study, pathogenesis related factors